The Effectiveness of Digital Accounting Practices on Goal Achievement for Thai Industrial Plants - Punchabhorn Srichanapun; Natnaree Thongdeepan; Punsa Ruannoy (Asian Journal of Business and Accounting, 2026)
Manuscript type: Research paper Research aims: This research examines the effects of digital accounting practices efficiency on goal achievement at Thai industrial plants. Design/Methodology/Approach: A quantitative survey was conducted using a structured questionnaire with 132 respondents. Data analysis employed descriptive statistics and the PROCESS macro for SPSS. Research findings: The findings revealed that digital accounting practice efficiency significantly enhances organisations value enhancement and financial information usefulness. These improvements, in turn, positively affect goal achievement. Furthermore, organisational value enhancement and financial information usefulness serve as mediators in the relationship between digital accounting efficiency and goal achievement. Theoretical contribution/Originality: Empirical evidence supports the resource-based theory, with relevance to Thai industrial plants. Practitioner/Policy implications: These findings underscore the importance of digital accounting practice efficiency, organisational value enhancement, and financial information usefulness in goal achievement for industrial plants. Research limitation: The study’s focus on industrial plants in Thailand, which may restrict the generalizability of the findings.